Vertical farming of hardy nursery stock: LED-driven propagation strategies compared with industry practice - Baghalian, Kambiz; Ranasingha, Ruvini (Frontiers in Plant Science, 2026)
Hardy nursery stock production relies on the propagation of semi-hardwood or hardwood cuttings, yet rooting success is often inconsistent due to species-specific constraints and environmental variability. This study examined how vertical farming systems influences early propagation traits in three evergreen woody ornamentals—Elaeagnus × ebbingei, Pittosporum tenuifolium, and Euonymus japonicus—representing varying rooting difficulty. Cuttings were propagated under ambient light (control) or two light-emitting diode (LED) treatments differing in red-to-blue ratio and intensity (7:1 at 100 μmol m-² s-¹; 9:1 at 140 μmol m-² s-¹). Fresh shoot weight, fresh root weight, and chlorophyll content were measured, and trait stability assessed via coefficients of variation. E. japonicus achieved highest biomass under the 7:1 ratio, while E. × ebbingei and P. tenuifolium performed best under ambient light. Chlorophyll declined under LEDs in all species but remained most stable in E. japonicus. Variability analysis indicated chlorophyll as the most stable trait, shoot biomass moderately variable, and root biomass the most plastic. Principal component analysis indicated that chlorophyll and biomass traits were regulated independently, suggesting that rooting responses were more closely associated with carbon allocation processes than with pigment stability. These results demonstrate that species-specific responses shape propagation outcomes, and tailored LED strategies can enhance rooting uniformity and efficiency.